Implementation of socio-scientific issues learning to improve students critical thinking skills - Defania Hasyyati Rosyidah; Hasan Subekti (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to describe the implementation of socio-scientific issues learning, critical thinking skills, and student learning responses. This research is quantitative. This pre-experimental study used the One Group Pretest Post-test Design. The subjects in this study were 23 students of class VIII B at UNESA YDWP Laboratory Middle School. The instruments used were observation sheets of learning implementation, critical thinking skills test sheets, and response questionnaire sheets. Data analysis techniques on learning implementation sheets and response questionnaires were calculated based on the mode value, then on critical thinking skills using t-test analysis and effect size. The study results showed that learning socio-scientific issues can be carried out in very good categories. Students' critical thinking skills have increased as indicated by the acquisition of the t-test of critical thinking skills tcount > ttable or 18.852 > 2.074 with a significance level of 0.000 <0.05, so H0 is rejected, and Ha is accepted. So, it shows a significant difference in value between the pretest and post-test scores. Calculating the effect size of critical thinking skills was also carried out with a value of 3.924 in the very large category so that socio-scientific issues learning effectively influenced critical thinking skills. The results of student responses agree on learning socio-scientific issues that are interesting, easy to understand, and useful for everyday life. Thus, there is an increase in students' critical thinking skills after applying socio-scientific issues learning.